Global transcriptome and targeted metabolite analyses of roots reveal different defence mechanisms against Ralstonia solanacearum infection in two resistant potato cultivars - Jose, Jeny; Éva, Csaba; Bozsó, Zoltán; Hamow, Kamirán Áron; Fekete, Zsófia; Fábián, Attila; Bánfalvi, Zsófia; Sági, László (Frontiers in Plant Science, 2023)
Ralstonia solanacearum (Rs), the causal agent of bacterial wilt disease in an unusually wide range of host plants, including potato (Solanum tuberosum), is one of the most destructive phytopathogens that seriously reduces crop yields worldwide. Identification of defence mechanisms underlying bacterial wilt resistance is a prerequisite for biotechnological approaches to resistance breeding. Resistance to Rs has been reported only in a few potato landraces and cultivars. Our in vitro inoculation bioassays confirmed that the cultivars ‘Calalo Gaspar’ (CG) and ‘Cruza 148’ (CR) are resistant to Rs infection. Comparative transcriptome analyses of CG and CR roots, as well as of the roots of an Rs-susceptible cultivar, ‘Désirée’ (DES), were carried out two days after Rs infection, in parallel with their respective noninfected controls. In CR and DES, the upregulation of chitin interactions and cell wall-related genes was detected. The phenylpropanoid biosynthesis and glutathione metabolism pathways were induced only in CR, as confirmed by high levels of lignification over the whole stele in CR roots six days after Rs infection. At the same time, Rs infection greatly increased the concentrations of chlorogenic acid and quercetin derivatives in CG roots as it was detected using ultra-performance liquid chromatography ‒ tandem mass spectrometry. Characteristic increases in the expression of MAP kinase signalling pathway genes and in the concentrations of jasmonic, salicylic, abscisic and indoleacetic acid were measured in DES roots. These results indicate different Rs defence mechanisms in the two resistant potato cultivars and a different response to Rs infection in the susceptible cultivar.